2017
DOI: 10.1111/jfs.12343
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of camel milk on Cronobacter sakazakii

Abstract: The objective of this study was to investigate the behavior of Cronobacter sakazakii in raw and pasteurized camel milk compared with bovine milk at different incubation temperatures. Pasteurized and raw camel milk was inoculated with a cocktail of two strains of C. sakazakii and incubated at 10°C, 25°C, and 37°C to be sampled at 0, 2, 4, 8, and 24 hr. Pasteurized bovine milk was treated similarly and used as a control. Raw and pasteurized camel milk showed more inhibitory effect against C. sakazakii at 25°C th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Similarly, S. Typhimurium and E. coli O157:H7 showed low survival properties in tabbouleh salad and eggplant dip when stored at 21°C compared to 4°C (Al‐Rousan et al, ; Osaili et al, ). Abusheliabi et al () also found that raw and pasteurized camel milk exhibited more inhibitory effect against Cronobacter sakazakii at 25°C than at 10°C.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, S. Typhimurium and E. coli O157:H7 showed low survival properties in tabbouleh salad and eggplant dip when stored at 21°C compared to 4°C (Al‐Rousan et al, ; Osaili et al, ). Abusheliabi et al () also found that raw and pasteurized camel milk exhibited more inhibitory effect against Cronobacter sakazakii at 25°C than at 10°C.…”
Section: Resultsmentioning
confidence: 96%
“…At the same time, raw and pasteurized camel milk has the capacity to inhibit Cronobacter sakazakii . As this bacterium can grow in powder milk, some authors think that it could be possible to use it in the production of infant formula [ 73 ], but such a possibility requires further investigation.…”
Section: Pasteurized Milkmentioning
confidence: 99%
“…Antimicrobial peptides have been detected in the milk of other food animal species including sheep and goats (111). A recent report that growth of C. sakazakii is inhibited by strong, inherent antibacterial factors in camel milk suggested they are likely derived from the protein component (105). A database assembled by Wang et al (112) lists 1,972 known antimicrobial peptides from animal sources, in addition to 321 from plants and many from fungi, protists or other life forms.…”
Section: Nisinmentioning
confidence: 99%